The push for independence in Catalonia. (October 2018) - Barrio, Astrid; Field, Bonnie
In 2017, Catalonia unilaterally declared independence from Spain. The independence push was not simply a bottom-up process wherein citizens increasingly demanded independence. Catalan political elites were more radical than voters and competitive outbidding to win hegemony in the pro-independence camp fuelled the independence push.